IMPROVEMENT OF STUDENTS‘ DISCIPLINE IN ENGLISH DISTANCE LEARNING THROUGH YOUTUBE AT JUNIOR HIGH SCHOOL - Nurhasanah, Henny (Jurnal Profesi Keguruan, 2024)
Discipline character is one of the many aspects of character education that needs to be developed. As a place of learning, Madrasahs are expected to be able to provide learning that can shape character for students. Problems at MTs N 1 Pati regarding character emerge when students take part in distance learning (PJJ). In practice, teachers during PJJ only used modules and PowerPoint sent via the WA group. But the longer, the child is getting bored in learning and the level of discipline decreases. In addition, there are many assignments that are not collected, when learning, many students are late and don't even attend for various reasons. After the author made learning videos using YouTube media, and discussion forums on the WA group, students were increasingly motivated in learning, in fact, almost all students were active in opening material on YouTube. Discipline begins to show a significant level of improvement, which occurred in the first week at 75%, in the fifth week it can increase to 97%. The increase in student discipline was followed by an increase in the collection of student assignments. Many assignments were collected in a timely manner, the collection of assignments in August and September 2020 showed a significant change from the first task which was originally 78%, in the fifth task it had reached 98%. . Apart from YouTube media which can improve children's discipline, the role of a student guardian and homeroom teacher is no less important in shaping the character of discipline.